Minimally invasive coronary artery bypass as an option for redo coronary surgery in a frail octogenarian - Kędziora, Anna; Konstanty-Kalandyk, Janusz; Litwinowicz, Radoslaw; Legutko, Jacek; Kapelak, Boguslaw; Piatek, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Minimally invasive direct coronary artery bypass (MIDCAB) is a method of surgical revascularization in which the left internal mammary artery (LIMA) is harvested to graft the left anterior descending artery (LAD) through a small incision on the chest wall (Figure 1 A). The procedure is performed without cardioplegia induced cardiac arrest and allows the burden of open-chest surgery to be avoided. Previous studies have shown excellent early and long-term results for MIDCAB performed either as a single procedure for an isolated LAD lesion [1] or as a step in hybrid revascularization with percutaneous coronary intervention to other significantly stenosed arteries [2]. Nevertheless, the data for the use of MIDCAB as a method of choice for re-do cardiac surgery are sparse.